2015
DOI: 10.2215/cjn.03000315
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Decline in Kidney Function

Abstract: Background and objectives The independent link between arterial stiffness and CKD remains unknown. We investigated the association of indicators of arterial stiffness with decline in kidney function.Design, setting, participants, & measurements We studied 3666 participants (mean age =65 years old; 58% women) from the Rotterdam Study. Pulse pressure (PP), carotid stiffness, and pulse wave velocity (PWV) were measured. We created genetic risk scores for PP and PWV. Annual declines in kidney function and incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 35 publications
5
115
1
9
Order By: Relevance
“…The mean baseline age of our cohort was younger than in other studies of the effect of arterial stiffness on GFR decline. 6,8,26 This finding suggested that arterial stiffness might be an early stage in the mechanism for accelerated GFR decline. We previously reported that baseline conventional BP per se did not accelerate age-related GFR decline in the RENIS cohort, 19 and the current investigation found the same results for ABP (Table 3).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The mean baseline age of our cohort was younger than in other studies of the effect of arterial stiffness on GFR decline. 6,8,26 This finding suggested that arterial stiffness might be an early stage in the mechanism for accelerated GFR decline. We previously reported that baseline conventional BP per se did not accelerate age-related GFR decline in the RENIS cohort, 19 and the current investigation found the same results for ABP (Table 3).…”
Section: Discussionmentioning
confidence: 81%
“…Three previous longitudinal, population-based studies of estimated GFR decline used carotid femoral pulse wave velocity (PWV). 6,8,26 Although none of them found an effect on the GFR decline rate as a continuous variable, increased PWV was associated with an increased odds ratios for rapid GFR decline in the AGES Reykjavik study and for incident chronic kidney disease stage 3 in the Health ABC study (Health, Aging, and Body Composition). 6,8 In contrast, there was no effect of PWV on incident chronic kidney disease stage 3 in the Framingham Offspring Study.…”
Section: Discussionmentioning
confidence: 93%
“…Нами получены данные о вза-имном негативном влиянии нарушений фильтраци-онной функции на артериальное ремоделирование при ХСН и ХБП. Вклад артериальной жесткости в развитие ХБП показан в исследовании Sedaghat S, et al [9]. В Rotterdam Study было найдено, что увеличе-ние жесткости в сонных артериях на 1 стандартное отклонение ассоциируется с увеличением риска раз-вития ХБП на 13% (95% ДИ, 1,05-1,22).…”
Section: таблицаunclassified
“…The high prevalence of CKD in older adults is attributable not only to the presence of traditional risk factors such as diabetes and hypertension but may also be the result of age-related functional changes that occur in the kidney [20]. Importantly, epidemiological studies have identified arterial stiffness (which increases with age) as a predominant risk factor for progressive GFR decline in older people [21,22]. We have previously shown TGF-β levels independently predict peripheral vascular disease in aged community-dwelling adults [23].…”
Section: Introductionmentioning
confidence: 99%